'Little bit afraid 'til I found how it was': children's subjective early school experiences in a disadvantaged community in Ireland. Issue 2 (4th March 2017) - O'Rourke, Claire; O'Farrelly, Christine; Booth, Ailbhe; Doyle, Orla
ABSTRACT: Research shows that children facing socioeconomic risk often have poorer skills at school entry, greater difficulty adjusting to school, more negative school experiences, and lower scholastic achievement, relative to their peers. However, the promotion of positive early school experiences is constrained by a lack of insight into disadvantaged children's own perspectives. To address this gap, this study interviewed 26 children living in a disadvantaged community in Ireland who had recently commenced formal schooling. Interviews included semi-structured questions and a draw-and-talk activity. Interview questions and drawings were analysed using the principles of thematic analysis and content analysis respectively, and the findings were integrated to identify four overarching themes. These included children's sense of self in school, what happens in school, the importance of peer relationships, and children's lives around school. The results provide reflection points for research and practice, such as the promotion of positive peer experiences and strong family–school connections.